2021
DOI: 10.1016/j.msea.2020.140725
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-induced hardening in an austenitic CrFeMnNi high-entropy alloy (HEA)

Abstract: Nitrogen is a well-known gamma-stabiliser in austenitic steels, also responsible for significant solid solution hardening of these materials. Yet, only few papers have studied its impact on austenitic high-entropy alloy (HEA) matrixes. This study focuses on a cobalt-free, non equimolar CrFeMnNi HEA doped with nitrogen. A series of alloys was cast under a nitriding atmosphere to promote nitrogen absorption into the liquid alloy. Study of as-cast alloys has shown nitrogen presence in solid solution up to 0.3 wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The beneficial effect of N on the systems CoCrFeMnNi and CrFeMnNi has been also documented by Xiong et at. [20] and Traversier et al [21], respectively, which the authors associate with, solid-solution strengthening, precipitation strengthening, and grain refinement [20].…”
Section: Effect Of C and N On The Mechanical Propertiesmentioning
confidence: 97%
“…The beneficial effect of N on the systems CoCrFeMnNi and CrFeMnNi has been also documented by Xiong et at. [20] and Traversier et al [21], respectively, which the authors associate with, solid-solution strengthening, precipitation strengthening, and grain refinement [20].…”
Section: Effect Of C and N On The Mechanical Propertiesmentioning
confidence: 97%
“…Since the nitride precipitation is formed, we can assume that the matrix of N0.3 HEA has solute nitrogen atoms as maximum solubility. The maximum solubility of nitrogen in Cantor HEA is reported as 0.18 wt.% (~0.72 at.%) [41]. Therefore, the ∆σ S without the effect of precipitation can be calculated as~89.3 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Recent works have shown that some single-phase High Entropy Alloys (HEA) exhibit excellent mechanical properties, radiation-resistance properties and phase stability making them potential candidates for structural applications [1][2][3][4][5][6][7][8][9][10]. However, many authors have traced the origin of these properties to the specific behaviour of dislocations [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Face-Centered Cubic (FCC) HEA, such as Cantor alloy consisting of equimolar CoCrFeMnNi composition exhibits excellent mechanical properties and improved irradiation resistance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Face-Centered Cubic (FCC) HEA, such as Cantor alloy consisting of equimolar CoCrFeMnNi composition exhibits excellent mechanical properties and improved irradiation resistance [1]. On the other hand, the presence of Cobalt excludes Cantor alloy from structural applications in nuclear reactors, due to the production of 60 Co radioisotope in in-service conditions [19,[29][30]. This is one of the reasons for the design of new Cofree HEA alloys, mainly from the CrFeMnNi family [19,[29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation